Aerobic Oxidation of Xylose to Xylaric Acid in Water over Pt Catalysts. Issue 13 (29th May 2018) - Sadula, Sunitha; Saha, Basudeb
Abstract: Energy‐efficient catalytic conversion of biomass intermediates to functional chemicals can make bio‐products viable. Herein, we report an efficient and low temperature aerobic oxidation of xylose to xylaric acid, a promising bio‐based chemical for the production of glutaric acid, over commercial catalysts in water. Among several heterogeneous catalysts investigated, Pt/C exhibits the best activity. Systematic variation of reaction parameters in the pH range of 2.5 to 10 suggests that the reaction is fast at higher temperatures but high C−C scission of intermediate C5 ‐oxidized products to low carbon carboxylic acids undermines xylaric acid selectivity. The C−C cleavage is also high in basic solution. The oxidation at neutral pH and 60 °C achieves the highest xylaric acid yield (64 %). O2 pressure and Pt amount have significant influence on the reactivity. Decarboxylation of short chain carboxylic acids results in formation of CO2, causing some carbon loss; however, such decarboxylation is slow in the presence of xylose. The catalyst retained comparable activity, in terms of product selectivity, after five cycles with no sign of Pt leaching. Abstract : Pulling the weeds : Energy‐efficient oxidation of lignocellulosic biomass xylose to xylaric acid, a promising precursor for glutaric acid, is studied systematically to elucidate factors that cause retro‐aldol C−C bond scission of the desired oxidation product and tune reaction parameters to achieve high xylaric acid yield.